2017
DOI: 10.1016/j.earlhumdev.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Quality of caregiver-child play interactions with toddlers born preterm and full term: Antecedents and language outcome

Abstract: Background Preterm birth may leave long-term effects on the interactions between caregivers and children. Language skills are sensitive to the quality of caregiver-child interactions. Aims Compare the quality of caregiver-child play interactions in toddlers born preterm (PT) and full term (FT) at age 22 months (corrected for degree of prematurity) and evaluate the degree of association between caregiver-child interactions, antecedent demographic and language factors, and subsequent language skill. Study De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 41 publications
1
21
0
5
Order By: Relevance
“…Eighteen eligible studies 48 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 with 18 effect sizes on measures of intensified or deliberate orienting to an object were included ( Figure 4 ). Preterm birth was associated with diminished focused attention (Cohen d , −0.28; 95% CI, −0.45 to −0.11; z , −3.25; P = .001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen eligible studies 48 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 with 18 effect sizes on measures of intensified or deliberate orienting to an object were included ( Figure 4 ). Preterm birth was associated with diminished focused attention (Cohen d , −0.28; 95% CI, −0.45 to −0.11; z , −3.25; P = .001).…”
Section: Resultsmentioning
confidence: 99%
“…During the past 50 years, a myriad of studies assessed the association between preterm birth and attention development in early life, but only a few reviews attempted to synthesize and generalize the findings. 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 Two notable reviews 83 , 84 from previous decades suggested that infants born preterm show less-optimal attention performance. However, because both reviews were nonsystematic and did not attempt a statistical synthesis, there was a necessity for a methodical review to revisit the important claims of the previous s...…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that the infants showed negative or non-interactive behaviors in relation to maternal intrusive behaviors, such as taking the hands to their mouths, closing their eyes upon mothers' kissing, sucking and physically restricting behaviors. There is evidence that mothers of premature infants have more intrusive and directive behaviors in their interaction with their infants compared to mothers of full-term infants (Agostini, Neri, Dellabartola, Biasini, & Monti, 2014;Loi et al, 2017). In this sense, identifying the roles that maternal behaviors play in interacting with their infant can contribute to interventions that help mothers identify these functions and develop an alternative repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have described parents of preterm infants as more active and attentive, responding to their infants’ attention and vocalizations more than parents of term infants ( Barratt et al, 1992 ; Brachfeld et al, 1980 ). Other studies have reported that parents of preterm infants respond to their infants less frequently, direct their infants’ attention more frequently, and are more intrusive and controlling than parents of term infants ( Forcada-Guex, Pierrehumbert, Borghini, Moessinger, & Muller-Nix, 2006 ; Garner, Landry, & Richardson, 1991 ; Loi et al, 2017 ). Few studies have examined infant and parental attention in a comparable manner across social partners, making it difficult to evaluate whether and how parental orienting and responding are influenced by infant attention and/or prematurity.…”
Section: Introductionmentioning
confidence: 95%